The influence of gross motor habits on the physical activity abilities of preschool students at Hudan Cendia kindergarten - Gamagita, Laras Putri; Yudasmara, Dona Sandy; Weningtyas, Anditri; Amelia, Dessy; Soenarti, Sri; Hanifah, Sukma Nur; Prasetyo, Rizal Dwi; Prayoga, Wahyu Surya (Universitas Negeri Malang, 2023)
Physical activity habits in children aged 3-5 are built based on motor skills intervention. Gross motor activity can increase the ability to move and involve children in physical activities outside the room. This needs to be known about surveillance of physical and gross motor activities of children aged 3-5 years. This study correlated physical activity and gross motor skills in students at Kindergarten Hudan Cendikia with 20 subjects in Kindergarten A. Data were obtained from filling out physical activity questionnaires using the Global Physical Activity Questionnaire (GPAQ) and gross motor skills tests using the Gross Motor Development Test-2 (TGMD-2) with the data analysis technique used is correlation analysis using SPSS and quantitative descriptive analysis. The results of this study were that there was no relationship between physical activity and gross motor skills in children aged 3-5 years with a significance value of 0.330 > 0.05, students at Kindergarten Hudan Cendikia had an average gross motor skill which was very good with moderate physical conditions, on student involvement in sedentary activities students have high average results.